2019
DOI: 10.1088/1361-6528/ab548f
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical nanostructured W-Cu composite with outstanding hardness and wear resistance

Abstract: Hierarchical nanostructured W-Cu composite with an average W size below 200 nm and nanocrystalline structure inside the W phase was obtained by refining the inner structure of the initial ultrafine powders combined with high-pressure spark plasma sintering. It revealed that an atomic scale combination can be formed at both the W grain boundaries and W/Cu interfaces. Accordingly, the nanostructured W-Cu composite exhibits twofold hardness and greatly improved wear resistance with satisfactory electrical conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…However, the debris on the UFG W–Cu composite were much smaller than that in the CCG W–Cu composite, which further led to much narrower grooves in the UFG W–Cu composite, since grooves were typically caused by the scratches of the worn debris. It can then be concluded that abrasive wear and fatigue wear are the dominant wear mechanisms for both UFG W–Cu and CCG W–Cu composites, which is also consistent with previously reported results [ 29 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…However, the debris on the UFG W–Cu composite were much smaller than that in the CCG W–Cu composite, which further led to much narrower grooves in the UFG W–Cu composite, since grooves were typically caused by the scratches of the worn debris. It can then be concluded that abrasive wear and fatigue wear are the dominant wear mechanisms for both UFG W–Cu and CCG W–Cu composites, which is also consistent with previously reported results [ 29 ].…”
Section: Resultssupporting
confidence: 92%
“…For both the UFG and CCG W–Cu composites, significant pile-ups can be found at both ends of the wear scar due to plastic deformation. However, the pile-ups of the CCG W–Cu composite were much larger than that in the UFG W–Cu composite because the UFG W–Cu had higher hardness and greater resistance to deformation [ 29 ]. In addition, the width and depth of the wear scar for the UFG W–Cu composite (0.69 mm, 25.65 μm) were also much smaller than that of the CCG W–Cu (0.78 mm, 32.82 μm), indicating a reduced wear rate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations